PELATIHAN PEMBUATAN BATIK MENGGUNAKAN TEKNIK ECOPRINT SEBAGAI BENTUK PENGABDIAN KEPADA MASYARAKAT KELURAHAN REMODONG INDAH - Tohir, Muhamad; Aryadinata, Ilham; Afandi, Naufal Dzakwan Putra; Tendri, Tendri; Syaphira, Putri; Bilastri, Bilastri; Taria, Leles; Saputri, Rescilia; Inayah, Sherin Sagita; Kiranti, Kiranti (Lembaga Penelitian dan Pengabdian kepada Masyarakat - Universitas Abdurachman Saleh Situbondo, 2024)
Nowadays there are many variations of techniques in making and developing batik, one of which is using materials from plants to make patterns. The ecoprint technique uses natural materials from plants to print patterns on fabric, thereby reducing dependence on chemicals and providing added value to local products. This activity is a form of our service to the community of Remodong Indah Village which aims to provide training and develop the potential of local wisdom and to introduce environmentally friendly batik techniques to the community in Remodong Indah Village. Indicators of the success of this activity are the availability of plant raw materials for making patterns, active participation of training participants, involvement of community leaders, activeness of participants, skills in carrying out the stages of the activity, and implementation of the program. The target of this community service activity is the residents of Remodong Indah Village, especially mothers. Data collection was carried out through observation and questionnaires. Data analysis was carried out descriptively. This can also be seen from the increase in knowledge and skills in making batik using the ecoprint technique as shown by the results of the questionnaire given during counseling and evaluation. This journal discusses the training process, methods used, training results, and the impact on the community in Remodong Indah Village. Keywords: Batik Making, Eco Print Technique